2001
DOI: 10.4049/jimmunol.167.12.6933
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Germline DSP2 Gene Accounts for All Apparent V-D-D-J Rearrangements in Newborn, But Not Adult, MRL Mice

Abstract: Anti-dsDNA autoantibodies in MRL mice contain a higher than average frequency of atypical complementarity-determining regions 3, including those made with D-D rearrangements. It has been reported that MRL mice have an intrinsically high frequency of creating VDDJ rearrangements; however, we show in this study that the majority of these apparent D-D rearrangements in B cell progenitors can be accounted for by a very novel germline DH gene in mice of the Ighj haplotype. This gene has the appearance of a D to D r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 30 publications
(30 reference statements)
2
17
0
Order By: Relevance
“…We previously reported a novel V H 7183 gene in MRL/lpr and C3H mice, both of which are Igh j haplotype (25). In this study, we have found this V H gene in another lupus-prone strain, NZB, which is also Igh j for most of the V H locus (56).…”
Section: Germline V H Gene Created By V H Replacementsupporting
confidence: 50%
See 4 more Smart Citations
“…We previously reported a novel V H 7183 gene in MRL/lpr and C3H mice, both of which are Igh j haplotype (25). In this study, we have found this V H gene in another lupus-prone strain, NZB, which is also Igh j for most of the V H locus (56).…”
Section: Germline V H Gene Created By V H Replacementsupporting
confidence: 50%
“…Furthermore, there have been reports of unusually high frequency of D-D rearrangements in two different strains of lupus-prone mice (5,6). We previously reported that we could only identify ϳ2-4% of rearranged sequences as having potential D-D rearrangements in CDR3 from adult bone marrow pre-B cells in both lupus-prone and nonautoimmune strains (25). We further showed that newborn sequences from these same strains displayed no D-D rearrangements (25).…”
Section: Paucity Of V-d-d-j Rearrangements and V H Replacement Eventsmentioning
confidence: 92%
See 3 more Smart Citations